Branching processes: Martingales and stopping rules

Martingale is an abstraction of "fair play." If a stochastic process is a martingale, some problems can be greatly simplified.

We continue our study of branching processes. \(X_n\) is the random variable representing the population size of the \(n\)-th generation (\(X_0 = 1\) is the initial condition).

See also:

Martingales

Consider the following conditional expectation: 

\[\mathbb{E}(X_{n+1}|X_0,X_1,\cdots,X_n) = \sum_{x}x\Pr(X_{n+1}=x|X_0,X_1,\cdots,X_n).\]

Here the sum is over all possible values of \(X_{n+1}\). Note that this conditional expectation itself is a random variable as it is conditioned on the random variables \(X_0, X_1, \cdots, X_n\) (not on their values). This expectations doesn't really depend on \(X_0,X_1,\cdots,X_{n-1}\), but it does depend on \(X_n\) (the Markov property!). Each individual out of \(X_n\) individuals produces \(\mu_1\) offsprings on average, so the above conditional expectation should be

\[\mathbb{E}(X_{n+1}|X_0,X_1,\cdots,X_n) = X_n\mu_1.\]

Let's introduce a new random variable:

\[Z_n = \frac{X_n}{\mu_n} = \frac{X_n}{\mu_1^n}.\]

Then, the above conditional expectation can be rearranged into

\[\mathbb{E}(Z_{n+1}\mu_1^{n+1}|X_0,\cdots,X_n) = Z_n\mu_1^{n+1}.\]

Cancelling the common factor \(\mu_1^{n+1}\), we obtain

\[\mathbb{E}(Z_{n+1}|X_0,\cdots,X_n) = Z_n.\tag{Eq:Martingale}\]

Thus, the conditional expectation \(Z_{n+1}\) is \(Z_n\). In general, a sequence of random variables \(\{Z_n\}\) that satisfies Eq. (Eq:Martingale) is called a martingale (with respect to the random variable sequence \(\{X_n\}\)).

The gambling martingale

The term "martingale" originates from a strategy in gambling (see Figure 1 below). A gambler bets 1 dollar in the first game. She doubles the bet in each subsequent game. That is, the bet is 2 dollars in the second game, 4 dollars in the third, etc. Assume that her first win is at the \(n\)-th bet. This means she wins \(2^n\) dollars after losing \(1 + 2 + 4 + \cdots + 2^{n-1} = 2^n - 1\) dollars. Thus, in total, she has won 1 (\(= 2^n - (2^n -1)\)) dollar. This is a guaranteed method of winning! (Not recommended for obvious reasons.)

Figure 1: The gambling martingale.


Let \(Z_n\) be the gambler's total asset (or debt) at the \(n\)-th bet. Each \(Z_n\) is a random variable. Their possible values are:
\[\begin{eqnarray} Z_0 &=& \{1\},\\ Z_1 &=& \{0, 2\},\\ Z_2 &=& \{-2, 0, 2, 4\},\\ Z_3 &=& \{-6, -4, -2, 0, 2, 4, 6, 8\},\\ &\vdots&\nonumber \end{eqnarray}\]
In general, \(Z_n = \{-2^n + 2, -2^2 + 4, \cdots, 2^n -2, 2^n\}\), or
\[Z_n = \{-2^n + 2m + 2 | m = 0, 1, 2, \cdots, 2^n - 1\}\]
for \(n = 1, 2, 3, \cdots\). Any one of these outcomes has a probability \(1/2^n\). Thus, the (unconditional) expectation of \(Z_n\) is
\[\mathbb{E}(Z_n) =\sum_{m=0}^{2^n-1}\frac{1}{2^n}(-2^n + 2m + 2) = 1.\]
The conditional expectation of, say, \(Z_2\) given \(Z_0, Z_1\) is calculated as follows (see Figure 1):
\[\begin{eqnarray} \mathbb{E}(Z_2|(Z_0, Z_1) = (1,2)) &=& 4\cdot\Pr(Z_2=4|(Z_0,Z_1)=(1,2)) + 0\cdot\Pr(Z_2=0|(Z_0,Z_1)=(1,2))\nonumber\\ & =& 4\cdot\frac{1}{2} + 0\cdot\frac{1}{2} = 2,\\ \mathbb{E}(Z_2|(Z_0, Z_1) = (1,0)) &=& 2\cdot\Pr(Z_2=2|(Z_0,Z_1)=(1,0)) + (-2)\cdot\Pr(Z_2=-2|(Z_0,Z_1)=(1,0))\nonumber\\ & = & 2\cdot\frac{1}{2} - 2\cdot\frac{1}{2} = 0. \end{eqnarray}\]
Hence,
\[\mathbb{E}(Z_2|Z_0, Z_1) = \{0, 2\} = Z_1.\]
Similarly (exercise!), the conditional expectation of \(Z_3\) given \(Z_0, Z_1, Z_2\) is
\[\mathbb{E}(Z_3|Z_0, Z_1, Z_2) = \{4, 2, 0, -2\} = Z_2.\]
In general, we have
\[\mathbb{E}(Z_{n+1}|Z_0, Z_1,\cdots, Z_n) = Z_n.\]
Thus, \(\{Z_n\}\) is a martingale with respect to itself.

Example (Eg:RW). Let \(X_n, n = 0, 1, 2, \cdots\) be the random variable for the position of a walker in a symmetric random walk with \(X_0 = 0\). Let's show that \(X_n\) is a martingale with respect to itself. That is,
\[\mathbb{E}(X_{n+1}|X_n) = X_n.\]
To show this, note that, given whatever value of \(X_{n}\), the value of \(X_{n+1}\) is either \(X_{n} + 1\) or \(X_{n} - 1\), each with probability \(\frac{1}{2}\). Therefore,
\[\mathbb{E}(X_{n+1}|X_n) = \frac{1}{2}(X_{n} + 1) + \frac{1}{2}(X_{n} - 1) = X_{n}.\]

Stopping rules

Example (Eg:Y). Consider a random process, \(\{X_r\}, r = 0, 1, 2\cdots.\) We decide to stop when a specified conditions are met.
  1. We may want to stop at a specific time \(r = T\). In this case, \(T\) is known, and \(\mathbb{E}(X_T)\) is of interest.
  2. We may want to stop when \(X_r\) becomes greater than or equal to a certain value. In this case, the value (or range) of \(X_T\) is known when the process stops, but the stopping time \(T\) is unknown, and we are interested in \(\mathbb{E}(T)\), the expected stopping time.
Consider a symmetric (Markov chain) random walk that starts at position \(k\). Let \(X_n, n = 0, 1, 2, \cdots\) be the random variable of the position of the walk at step \(n\). The random variable \(Y_n = X_n^2 - n\) is a martingale with respect to \(X_n\). That is,
\[\mathbb{E}(Y_{n+1} | X_{n}) = Y_n.\]
To see this, note that \(X_{n+1}\) is either \(X_n + 1\) or \(X_n - 1\), each with probability \(\frac{1}{2}\) (See the above example (Eg:RW)). Therefore,
\[\begin{eqnarray} \mathbb{E}(Y_{n+1}|X_n) &=& \frac{1}{2}(X_n + 1)^2 + \frac{1}{2}(X_n-1)^2 - (n + 1)\\ &=& X_n^2 - n = Y_n.\end{eqnarray}\] □

Theorem (Stopping Theorem)

If \(\{Z_n\}\) is a martingale with respect to \(\{X_n\}, n = 0, 1, \cdots\) and \(T\) is a defined stopping time, and
  1. \(\Pr(T < \infty) = 1\),
  2. \(\mathbb{E}(|Z_T|) < \infty\),
  3. \(\mathbb{E}(Z_n|T>n)\Pr(T > n) \to 0\) as \(n \to \infty\),
then \(\mathbb{E}(Z_T) = \mathbb{E}(Z_0)\).
Proof. Omitted. (See also Optional stopping theorem.) ■

Example. The symmetric random walk starts at \(X_0 = k\). Suppose the walk stops at step \(n = T\) if either \(X_T = 0\) or \(X_T = a\) for some \(a\) is satisfied (This is the Gambler's Ruin problem. Remember?). What is the expected stopping time, \(\mathbb{E}(T)\)? From the above Example (Eg:Y), we know that \(Y_n = X_n^2 - n\) is a martingale with respect to \(X_n\). We can show that this martingale satisfies all the conditions for the Stopping Theorem (exercise!). Thus,
\[\mathbb{E}(Y_T) = \mathbb{E}(Y_0) = \mathbb{E}(X_0^2 - 0) = k^2.\]
On the other hand, we have
\[\begin{eqnarray} \mathbb{E}(Y_T) &=& \mathbb{E}(X_T^2 - T)\\ &=& \mathbb{E}(X_T^2) - \mathbb{E}(T)\\ &=& [0\times\Pr(X_T = 0) + a^2\times\Pr(X_T = a)] - \mathbb{E}(T)\\ &=& a^2\times\frac{k}{a} -\mathbb{E}(T) = ak - \mathbb{E}(T) \end{eqnarray}\]
where we used the result from the Gambler's Ruin Problem that \(\Pr(X_T = a) = k/a\). By combining these results, we have the expected stopping time:
\[\mathbb{E}(T) = k(a - k).\]

Comments

Popular posts from this blog

Open sets and closed sets in \(\mathbb{R}^n\)

Euclidean spaces

Newton's method